Long-Term Outcomes in Patients with ST-Elevation Myocardial Infarction: A Comparative Study of Direct Admissions versus Interhospital Transfers—Insights from a Single-Center Experience in the United Kingdom - Tarek Abdeldayem; Ashan Gunarathne (International Journal of Clinical Practice)
Background. Primary percutaneous coronary intervention (PPCI) is the treatment of choice for patients with ST-elevation myocardial infarction (STEMI). Delayed reperfusion leads to increased morbidity and mortality. Secular trends in the impact of interhospital transfers (IT) on long-term mortality in the United Kingdom (UK) have not been previously investigated. We analyzed the impact of IT on 5-year mortality in STEMI patients admitted to a tertiary care center in the UK (East Midlands North). Methods. Data of STEMI patients admitted to Nottingham University Hospitals NHS Trust from 2011 to 2016 were acquired from the National Institute for Cardiovascular Outcomes Research dataset (NICOR) and then combined with local patient-level data and mortality data from National Statistics. The baseline characteristics and mortality data of the interhospital transfer (IT) group were compared to those of a gender and age-matched direct admission (DA) group. Results. Of the total cohort (N = 2386), 29.9% of patients were admitted to the PPCI center via the interhospital transfer (IT) route. Cardiovascular risk profiles in both DA and IT groups were comparable. Five-year Kaplan–Meier (KM) survival analysis revealed better survival in the direct admission group (83% vs. 77.3%; p≤0.001). In multivariate analysis, increased mortality was associated with severe left ventricular impairment (HR 4.7, 95% CI 2.9–7.6), the presence of cardiogenic shock (HR 3.6 (2.7–4.8)), chronic kidney disease (HR 2.56 (1.4–4.5)), smoking (HR 1.45 (1.1–1.8)), male gender (HR 1.7 (1.4–2.01)), and diabetes (HR 1.4 (1.07–1.8)). The radial access and call-to-balloon time less than 120 minutes were also associated with lower mortality (HR 0.52 (0.43–0.63): HR 0.75 (0.61–0.92)). Conclusion. Despite advancements in communication, technology, patient education, transportation systems, and guidelines within the UK’s NHS over the last decade, the delays incurred by IT for STEMI patients remain substantial and are associated with a poor prognosis.